Heuristic potential of the dialogue (on the material of the cultural creation project U. Eco and J.-C. Carrière "Do not hope to get rid of books!") - E. I. Onishchenko, (Ukrainian Cultural Studies, 2017)
The article analyzes the culture-creative project by J.-C. Carrière and U. Eco "Do not hope to get rid of books!" The aim is to study the heuristic potential of the dialogue and to reveal the specifics of the creative process based on it. The methodology of the study includes the use of an interdisciplinary approach that relies on the achievements of cultural studies, aesthetic theory by both Ukrainain and foreign authors. Theoretical and practical parity personified by U. Eko and J.-C. Carrière leads to organic and almost imperceptible, the transition of the interlocutors from one topic to another, prompting the reader to reflect on certain "cultural issues", which, at times, are more than paradoxical. The scientific novelty lays in the disclosure of the specifics of a book as a cultural phenomenon, accentuating significantly. The potential of dialogue for understanding the dynamics and specifics of the creative process, the emotional state of the artist, the stimulilation of his creativity, the phenomenon of fantasy. The theoretical possibilities discovered in the process of analysis of this phenomenon stimulated exploration of the specificity of the transition from the language of the figurative types of art and architecture to the language of literature, mainly "fitting" the extrasis in the field of semiotic issues. This, in turn, led to the speculation regarding the reproduction of one type of art by means of another, thus revealing new aspects in the study of synthesis and sinews. Observations that are expressed in the pages of the "Do not Expect to Get Rid of Books!" dialogs not only expand, but also, to a large extent, change the angle of the analysis of the extrasis. The interpretation, which formally conflicts with the authentic principle, actually plays an important cultural role. It is on this correlation of the authentic and interpretative and emphasizes U. Eko's attention, considering it as the determining factor of the extrasis. The practical importance of the dialogue "Do not expect to get rid of books!", except for the cultural worth, has a powerful stimulating start, and its analysis is able to activate theoretical research, expanding, and sometimes - updating the range of modern Ukrainian humanitaristics.
Keywords: dialogue, cultural creation, U. Eco, J.-C. Carrière, book